Over 3 in 4 Adults Potentially Subject to Medicaid Work Requirements May Already Have a Route to Exclusion or Compliance - Joshua Varcie; Shamik Bhat; Teddy Knox; Heather Howard (Health Affairs Scholar, 2026)
Abstract Introduction Starting in 2027, 18.5 million Medicaid enrollees will likely be subject to new work requirements that could lead to significant coverage losses. Methods Using American Community Survey data, we estimate the share of the population of interest that will have a route to exclusion from or compliance with the requirements. We also explore how rates of exclusion from or compliance with work requirements vary by state and demographic group. Results We find that 46 percent of those in our proxy population will meet the criteria for at least one exclusion, 58 percent will meet the criteria for compliance, and 78 percent will have at least one route to exclusion or compliance. The “exclusion or compliance” share varies from 70 percent in New York to 94 percent in North Dakota. It also varies by demographic group, as women and younger adults are more likely than their counterparts to have a route to exclusion or compliance. Conclusion The large "exclusion or compliance" share implies that an important driver of coverage loss will be states’ capacity to verify exclusions or compliance, as less than 1 in 4 enrollees are estimated to not have a route to exclusion or compliance.